2017
DOI: 10.1093/cid/cix184
|View full text |Cite|
|
Sign up to set email alerts
|

The Lysis of Pathogenic Escherichia coli by Bacteriophages Releases Less Endotoxin Than by β-Lactams

Abstract: SummaryBacteriophages kill bacteria very rapidly. Bacteriophage-induced endotoxin release could be an issue during phage therapy. We show that bacteriophages stop cell growth more rapidly than do β-lactams, resulting in a lower endotoxin release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 47 publications
1
50
1
2
Order By: Relevance
“…However, in this particular case, we overcame these hurdles and did not observe any discernible adverse clinical events. For example, concerns have arisen about the possibility that an accelerated lysis of Gram-negative bacterial pathogens could release clinically significant levels of endotoxin (27,28). A parallel concern can be made for administration of some antibiotics or any other alternative treatment that could lead to rapid, widespread cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this particular case, we overcame these hurdles and did not observe any discernible adverse clinical events. For example, concerns have arisen about the possibility that an accelerated lysis of Gram-negative bacterial pathogens could release clinically significant levels of endotoxin (27,28). A parallel concern can be made for administration of some antibiotics or any other alternative treatment that could lead to rapid, widespread cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the use of lytic phages can induce a rapid bacterial lysis, which can lead to a release of endotoxin, possibly causing a Jarisch‐Herxheimer reaction or an immunologic reaction to the release of endotoxin during antibiotic treatment . However, lytic phages induce less endotoxin release than B‐lactam antibiotics . Close follow‐up of the effect of phage therapeutic products in the human host is essential.…”
Section: Phage Therapymentioning
confidence: 99%
“…Several studies have observed waterborne endotoxin release during inactivation of Gram-negative bacteria (Dufour et al, 2017;Zhang et al, 2016;Sreeja and Shetty, 2016). The results of these works verify that embedded endotoxins can be released into the environment after the death of bacteria or cells.…”
Section: Introductionmentioning
confidence: 99%